The labour market impacts of leaving education when unemployment is high: Evidence from Britain - Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We estimate the effects of initial labour market entry conditions on a range of subsequent job outcomes for men and women who entered the British labour market between 1991 and 2009, using data from the British Household Panel Survey and its successor Understanding Society. We find that the unemployment rate on leaving full-time education has large impacts on initial labour market outcomes including status, wages and employment stability, which persist over the subsequent ten years. These effects are more pronounced for men than women and indicate that young people entering the labour market during the current period of economic stagnation will suffer a lasting scar as a consequence.
Keywords: C23; J22; J23; J31; J64; 330; Initial labour market conditions; wage determination; job quality; business cycle; panel data; BHPS; UKHLS